Fecal microbiota transplantation: great potential with many challenges - Kellermayer, Richard (Transl Gastroenterol Hepatol, 2019)
In January of 2019, Samuel P. Costello and colleagues published a wonderfully executed, double blind placebo-controlled trial on fecal microbiota transplantation (FMT) versus autologous stool as placebo in mild to moderately active adult ulcerative colitis [UC: one type of inflammatory bowel disease (IBD)] patients. This review-commentary examines the current state of knowledge on human gut microbiome (live microbiota + their products and surrounding environment, i.e., fecal matter) and microbial therapeutics from a gastrointestinal (GI) clinician’s standpoint. The varied forms of dysbiosis as the target of FMT, recipient donor and placebo considerations are also discussed in respect to randomized control trials in IBD [and the lack thereof in Crohn’s disease (CD)] with this unconventional treatment modality.